(untitled) (Research, Society and Development, 2020)
The course in Technology in Systems Analysis and Development at the Federal Institute of Goiás Campus Iporá is in person, divided into 6 periods, with a workload of 2,270 hours, with 33 mandatory subjects, 200 hours of optional subjects, 120 hours of complementary activities and 150 hours development of course work. The curricular matrix of the course determines an overview of the course portraying the periods and their respective disciplines, the course work, the complementary activities, the workload and the partial certificates with their respective hours. In this sense, the present work aims to describe some software developed by the students of the course as well as to relate the contents of some disciplines in software development. Methodologically, the study is classified as being of a qualitative nature, through the realization of an experience report with the students of the Technology in Analysis and Systems Development course at the Federal Goiano Institute, demonstrating the stages of the software development process. It was found, therefore, that the development and use of the contents of the subjects, contributes to the execution of the development activities and to the quality of the works developed.